1992
DOI: 10.1083/jcb.119.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gap junction and adherens junction assembly by connexin and A-CAM antibodies.

Abstract: Abstract. We examined the roles of the extracellular domains of a gap junction protein and a cell adhesion molecule in gap junction and adherens junction formation by altering cell interactions with antibody Fab fragments. Using immunoblotting and immunocytochemistry we demonstrated that Novikoff cells contained the gap junction protein, cormexin43 (Cx43), and the cell adhesion molecule, A-CAM (N-cadherin). Cells were dissociated in EDTA, allowed to recover, and reaggregated for 60 min in media containing Fab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
202
0
6

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(217 citation statements)
references
References 52 publications
9
202
0
6
Order By: Relevance
“…Based on the observation that presumptive migratory cells became uncoupled, we postulate that keratinocyte activation may be partly initiated by the loss of connexin expression and a concomitant decrease in GJIC. The molecular mechanisms by which GJIC affect activation are not known although the modulation of cell-cell adhesion subsequent to the inhibition of GJIC could be involved (Meyer et al, 1992;Paul et al, 1995). The second aspect of wound repair that correlated with altered GJIC is the restoration of normal epidermal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that presumptive migratory cells became uncoupled, we postulate that keratinocyte activation may be partly initiated by the loss of connexin expression and a concomitant decrease in GJIC. The molecular mechanisms by which GJIC affect activation are not known although the modulation of cell-cell adhesion subsequent to the inhibition of GJIC could be involved (Meyer et al, 1992;Paul et al, 1995). The second aspect of wound repair that correlated with altered GJIC is the restoration of normal epidermal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the presence of low levels of ZO-1 at the edge of Cx43-GFP plaques could result indirectly via macromolecular associations between GJs and other cell-cell junctions that incorporate ZO-1. Adherens junctions are logical candidates in this respect as they are known to play a pivotal role in GJ stability (Hertig et al 1996;Jongen et al 1991;Li et al 2005;Meyer et al 1992;Musil et al 1990;Wei et al 2005) and cadherin-associated catenin complexes have been shown to bind both Cx43 (Ai et al 2000;Wei et al 2005) and ZO-1 (Itoh et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of both the AJ and the GJ can be blocked with the use of antibodies against either N-cadherin or Cx43 (26), and Cx43 can be transported directly to existing AJ sites through microtubules (27). Cx43 has also been reported to promote endothelial attachment of leukocytes induced by cytokines or tumor cells during metastasis when it was overexpressed (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%